Indigestible Fictions: Hunger, Infanticide and Gender in Paola Masino's Fame and Massimo Bontempelli's La fame - Cesaretti, Enrico (Spunti e Ricerche, 2016)
The question of the intellectual exchange that took place during the life-long relationship between Paola Masino and Massimo Bontempelli and the presence of thematic and ideological analogies between some of their respective works has been repeatedly mentioned and, yet, rarely addressed in detail by scholars of Italian modernist literature. Dated and necessarily imprecise attempts to evaluate Masino's debt to her older and established companion or to assess whether her original writing style was influenced by Bontempelli's "realismo magico", have been replaced in more recent times by the realization – supported especially by the study of the intense correspondence between the two writers and with other figures -- that such an influence was not one-sided.